Building a Survey Tool to Assess Consumers’ Perception and Behavior Towards Green Consumption - Dũng, Vũ Anh; Anh, Nguyễn Thị Ngọc; Huyền, Nguyễn Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 29 No 2, 2013)
Abstract. Studies on green consumption behavior inVietnamare neither popular nor conducted carefully, especially empirical studies. With the aim of contributing to this research field, this paper adopts a new approach to find out consumers’ perception and behaviors towards green consumption by constructing a survey tool. Based upon the conceptual framework developed as a combination of determinants affecting green consumption found in previous studies and Ajzen’s Theory of planned behavior, a sample questionnaire for survey has been designed and pre-tested. The paper also provides guidelines for question design, trials and adjustments. Keywords: Green consumption, influential factors, questionnaire, survey.